The Role Of Millennial And Gen Z Preachers On Social Media In Promoting Moderate Islamic Views: Implications For Islamic Education In The Digital Era - Rokimin; Sita Husnul Khotimah; Fatmawati; Nunung Khoiriyah; Armawati Arbi; Kalsum Minangsih (IJGIE (International Journal of Graduate of Islamic Education), 2026)
This study investigates the pivotal role of Millennial and Gen Z preachers in promoting moderate Islam through social media platforms such as Instagram, YouTube, and TikTok, and examines the consequent implications for Islamic education in the digital era. The primary objectives are to analyze the strategies these young preachers employ to convey inclusive religious messages, to assess the impact of their digital da'wah on youth audiences, and to critically explore the challenges of maintaining theological depth within the attention-driven economy of social media. Methodologically, this research employs a qualitative phenomenological approach. Data were collected through in-depth interviews with 15-20 young preachers and subjected to systematic thematic analysis, complemented by a structured content analysis of their social media posts to examine the practical negotiation of moderate messaging online. The findings reveal that while these preachers successfully utilize engaging, innovative formats to broaden the reach of tolerant Islamic values, their practice is fundamentally reconfigured by the platform's logic. The research critically identifies the emergence of "media religious capital," where metrics of visibility and engagement often substitute for traditional religious authority, precipitating a risk of religious commodification. This dynamic creates a central tension: the necessity for algorithmic appeal and virality can compromise pedagogical integrity and dilute theological substance in favor of stylistic trends. Consequently, the study underscores the urgent need for enhanced religious literacy and specific training in digital ethics for content creators. It recommends fostering formal collaborations between Islamic educational institutions and digital preachers to anchor online discourse in scholarly depth. For future research, it is imperative to develop models of digital pedagogy that harmonize inclusivity with theological rigor and to longitudinally evaluate the impact of social media preaching on religious literacy and identity formation among young Muslims.